(untitled) (Knjiženstvo, journal for studies in literature, gender and culture, 2023)
The Feminist Challenge to the Socialist State in Yugoslavia / Zsófia Lóránd. – Palgrave Macmillan, 2018. – 285 str. – ISBN 978-3-319-78223-2 (e-book)